Early effects of selective serotonin reuptake inhibitors (SSRIs) on cornea and lens density in patients with depression. Issue 4 (2nd October 2019) - Karaküçük, Yalçın; Beyoglu, Abdullah; Çömez, Aysegül; Orhan, Fatma Özlem; Demir, Merve
ABSTRACT: PURPOSE: To investigate the effects of SSRIs on cornea and lens density, intraocular pressure (IOP) and anterior chamber parameters, including anterior chamber volume (ACV), anterior chamber depth (ACD), corneal volume (CV) and central corneal thickness (CCT), in patients with depression during a three-month follow-up period. METHOD: In this prospective study, 31 total patients, who were prescribed SSRIs for depression, were recruited. Sertraline, 50 mg/daily, was given to ten patients; 11 received Escitalopram, 10 mg/daily; and ten were treated with Fluoxetine, 20 mg/daily. The parameters recorded were corneal density (CD), lens density (LD), IOP, ACV, ACD, CV and CCT at the start of treatment, as well as at one-week, one-month, and three-month follow-ups. RESULTS: The study revealed that there was no risk of cataract development from three months of SSRI intake. Significant decrease in ACD was recorded at the one-week follow up; however, after three months, this decrease was insignificant compared to the baseline. ACV, CV, CCT, CD and LD showed no significant alterations in any of the follow up examinations over the three-month period. IOP, however, significantly fell (a P value of 0.004). CONCLUSION: In this study, SSRI use does not seem to be associated with an increased risk of cataract or glaucoma or with changes in CD and LD. Long-term follow-up is necessary to determine the actual risk of cataract or glaucoma with SSRI intake.